Evaluation of Processes Affecting the Variation of Groundwater Quality in Quang Nam, Da Nang, Vietnam - Nam Long, Phan; Thi Ngoc Anh, Nguyen; The Vinh, Bui; Thu Van, Can; Thu Thao, Nguyen; Thi Thu Thuy, Huynh (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4DO - 10.25073/2588-1094/vnuees.4693, 2021)
Groundwater quality is vulnerable to various processes. In this study, processes affecting groundwater quality were evaluated in coastal aquifers of Quang Nam - Da Nang (QNDN). A chemical data of 426 groundwater samples from 27 monitoring wells in the period 2011-2018 were analyzed. Principal Components Analysis (PCA) and Base Exchange Indices (BEX D ) were applied for the evaluation. The PCA results suggested the influences of natural processes and anthropogenic activities on the groundwater quality. Seawater influence contributed to the dominant ions in groundwater; mineral weathering and dissolution mainly increased the alkalinity, Ca 2+ , and Mg 2+ ; SO 4 2- reduction explained the low SO 4 2- in the groundwater; and reductive dissolution of Fe (hydroxides) caused Fe exceeding WHO’s drinking standard. Intensive groundwater abstraction generated up coning of saline groundwater; discharge from agricultural practices, industrialization, and urbanization were considered as sources of high NO 3 - in groundwater. The integration of monitoring data and BEX D gave a better interpretation of salinization and freshening, which can be masked by the memory effects of seawater transgression and regression in history.